2021
DOI: 10.3389/ffgc.2021.695269
|View full text |Cite
|
Sign up to set email alerts
|

Site Characteristics Mediate the Relationship Between Forest Productivity and Satellite Measured Solar Induced Fluorescence

Abstract: Solar-Induced Chlorophyll Fluorescence (SIF) can provide key information about the state of photosynthesis and offers the prospect of defining remote sensing-based estimation of Gross Primary Production (GPP). There is strong theoretical support for the link between SIF and GPP and this relationship has been empirically demonstrated using ground-based, airborne, and satellite-based SIF observations, as well as modeling. However, most evaluations have been based on monthly and annual scales, yet the GPP:SIF rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 72 publications
(86 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, Yazbeck et al. (2021) demonstrated that SIF did not reliably capture daily‐scale reductions in GPP due to water stress at multiple flux tower sites. Wohlfahrt et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Yazbeck et al. (2021) demonstrated that SIF did not reliably capture daily‐scale reductions in GPP due to water stress at multiple flux tower sites. Wohlfahrt et al.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the strong correlations reported between SIF and GPP at seasonal and diurnal timescales, uncertainties remain in the mechanistic relationship between SIF and GPP (Ryu et al, 2019), and in how that relationship changes across different ecosystems and spatiotemporal scales. Several studies have found that SIF over cropland is more closely tied to absorbed PAR (APAR) than to GPP (Miao et al, 2018;Yazbeck et al, 2021), and Zeng et al (2019) broadly demonstrated that SIF is strongly influenced by canopy structure and changes in f esc . SIF is also dependent on the fluorescence yield of the photosystems, which can itself be influenced by light and biological conditions (Baker, 2008), further complicating its relationship with GPP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the strong correlations reported between SIF and GPP at seasonal and diurnal timescales, uncertainties remain in the mechanistic relationship between SIF and GPP , and in how that relationship changes across different ecosystems and spatiotemporal scales. Several studies have found that SIF over cropland is more closely tied to absorbed PAR (APAR) than to GPP (Miao et al, 2018;Yazbeck et al, 2021), andZeng et al (2019) broadly demonstrated that SIF is strongly influenced by canopy structure and changes in fesc. SIF is also dependent on the fluorescence yield of the photosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Several satellite-based studies have used SIF to observe the impacts of moderate to severe drought (Li et al, 2020;Song et al, 2018;Yoshida et al, 2015); nonetheless, observations of SIF tend to be less sensitive to interannual variability in GPP during summer and may not show the impacts of mild stress (Butterfield et al, 2020). Furthermore, Yazbeck et al (2021) demonstrated that SIF did not reliably capture daily-scale reductions in GPP due to water stress at multiple flux tower sites. Wohlfahrt et al (2018) showed that local scale observations of SIF over a Mediterranean pine forest decoupled from GPP under environmental stress and suggested that much of the strong correlation between SIF and GPP in this ecosystem was driven by a shared dependence on APAR, calling into question the detectability of stress-induced changes in GPP from SIF observations.…”
Section: Introductionmentioning
confidence: 99%